Can higher education reduce inequality in developing countries? - Abebe Shimeles (IZA World of Labor, 2016)
Developing countries often face two well-known structural problems: high youth unemployment and high inequality. In recent decades, policymakers have increased the share of government spending on education in developing countries to address both of these issues. The empirical literature offers mixed results on which type of education is most suitable to improve gainful employment and reduce inequality: is it primary, secondary, or tertiary education? Investigating recent literature on the returns to education in selected developing countries in Africa can help to answer this question.
Keywords: I24; I26; 330; tertiary education; youth unemployment; returns to education; asset inequality